Avaliação de métodos de calibração do modelo oryza para estimar produtividade do arroz irrigado - Castro, João Rodrigo de (2020)
Brazil is one of the largest world producers of rice, being the largest production outside of Asian continent. Seventy percent of this production is concentrated in the southern states, where temperature availability and solar radiation are ideal. However, production concentrated in only one region is a matter of concern from the perspective of food security. Therefore, identifying and understanding the yield gaps outside of subtropical region becomes an important task. Crop model simulation is a tool that allows this assessment. In order to propose calibration processes for the ORYZA irrigated rice crop model, the dynamic of photoassimilated allocation were adjusted considering two environments: subtropical and tropical. Experimental data from five trials located at Subtropical (Cachoeirinha / RS) and Tropical (Goianira / GO) environments, for both cultivars, BRS Catiana and IRGA 424, were used. The ORYZA partition dynamic of assimilate were calibrated using information obtained in the experiments (phenological events dates and dry mass). The results obtained indicate that the use of both environments in the calibration, proposed in this study, performed better than default model calibration. The simulated yield for BRS Catiana cultivar with new partitioning parameters showed an improvement of 10% compared with the default ORYZA partitioning parameters. On the other hand, ORYZA model failed to describe satisfactorily the dynamics of mass allocation for leaves, due to the delay in leaf emission, suggesting that it could be related to photoperiodism.